Comprehension of action negation involves inhibitory simulation - Foroni, Francesco; Semin, Gün R. (Frontiers in Human Neuroscience, 2013)
Previous research suggests that action language is comprehended by activating the motor system. We report a study, investigating a critical question in this research field: do negative sentences activate the motor system? Participants were exposed to sentences in the affirmation and negation forms while the zygomatic muscle activity on the left side of the face was continuously measured (Electromyography technique: EMG). Sentences were descriptions of emotional expressions that mapped either directly upon the zygomatic muscle (e.g., “I am smiling”) or did not (e.g., “I am frowning”). Reading sentences involving the negation of the activity of a specific muscle (zygomatic major—“I am not smiling”) is shown to lead to the inhibition of this muscle. Reading sentences involving the affirmative form instead (“I am smiling”) leads to the activation of zygomatic mucle. In contrast, sentences describing an activity that is irrelevant to the zygomatic muscle (e.g., “I am frowning” or “I am not frowning”) produce no muscle activity. These results extend the range of simulation models to negation and by implication to an abstract domain. We discuss how this research contributes to the grounding of abstract and concrete concepts.